Fungi of entomopathogenic potential in Chytridiomycota and Blastocladiomycota, and in fungal allies of the Oomycota and Microsporidia - Agata Kaczmarek; Mieczysława I. Boguś (IMA Fungus)
Abstract The relationship between entomopathogenic fungi and their insect hosts is a classic example of the co-evolutionary arms race between pathogen and target host. The present review describes the entomopathogenic potential of Chytridiomycota and Blastocladiomycota fungi, and two groups of fungal allies: Oomycota and Microsporidia. The Oomycota (water moulds) are considered as a model biological control agent of mosquito larvae. Due to their shared ecological and morphological similarities, they had long been considered a part of the fungal kingdom; however, phylogenetic studies have since placed this group within the Straminipila. The Microsporidia are parasites of economically-important insects, including grasshoppers, lady beetles, bumblebees, colorado potato beetles and honeybees. They have been found to display some fungal characteristics, and phylogenetic studies suggest that they are related to fungi, either as a basal branch or sister group. The Blastocladiomycota and Chytridiomycota, named the lower fungi, historically were described together; however, molecular phylogenetic and ultrastructural research has classified them in their own phylum. They are considered parasites of ants, and of the larval stages of black flies, mosquitoes and scale insects.